A Impact of Anti-Müllerian Hormone, Oxidative Stress and Lipid Profile Levels on Female Fertility - Kadhim , Hawraa Mahdi (Medical Science Journal for Advance Research, 2025)
Background: Infertility also termed as a medical ailment of the reproductive system, hinders a person from conceiving. Anyone can develop this and its causes are many. Infertility is of three types: primary, secondary and unexplained. This blog will elaborate on the different types of infertility that stems from both males and females and try to unfold the complexities that come with this sensitive issue. Some common infertility causes include an irregular cycle of ovulation (the release of an egg on a monthly basis), low-quality semen, and blocked or damaged fallopian tubes. Objectives: The plasma levels of anti-Müllerian hormone, oxidative stress, and lipid profile of women with reproductive issues will be examined in this study. Materials and Methods: The case-control study included a total of 45 women who were healthy and 45 women who were unable to conceive World Health Organization. The study took place in the private clinic and the Babylon Teaching Hospital for Maternity and Children, which is located in Hilla City, and took place between the 1st of October 2023 to the 13th of December 2024. The enzyme-linked immunosorbent assay was used for the measurement of serum concentrations of the hormone whilst the SPSS software was used for the performing the statistical analysis. Results: After conducting the research, it came to light that unlike the control group, patients in comparison had significantly diminished levels of the anti-miillerian hormone, while also displaying substantially elevated levels of oxidative stress and lipid profiles in the serum (p <0.05). Conclusion: The serum levels of the anti-miillerian hormone present in women suffering from infertility were lower than average, correlating with the high levels of oxidative stress. These findings indicate that oxidative stress is an important factor in most of the infertility pathogenesis mechanisms described in this manuscript.